Flash卡媒体对提高圣约翰高中二年级学生的汉语词汇记忆能力的效果分析 - Monica, Irene; Iden, Sabinus (Confucius Institute Universitas Sebelas Maret, 2024)
The ability to remember vocabulary is essential for learning a foreign language, especially Chinese. If we can master and retain the vocabulary we study, it becomes easier to acquire listening, speaking, reading, and writing skills. To enhance vocabulary retention, suitable learning methods are required, one of which is the use of Flash Cards as a learning medium. The author conducted a quantitative study with students from Class A and Class B in the second grade of St. John High School. Data was collected using pre-test and post-test methods, along with interviews. After each lesson, the author presented the students with Flash Card images for each vocabulary item. The results of this study indicate that Flash Card media helps improve students' vocabulary retention. According to test results, students achieved an average vocabulary retention rate of 95.49%. The use of Flash Card media as a teaching method allows students to remember vocabulary more effectively.